Molecular Markers and Their Applications in the Construction of Genetic Linkage Maps and Analysis of Monogenic and Quantitative Traits in Oil Palm - Rajinder Singh (2005)
Molecular breeding is well suited to a perennial crop, like oil palm, in which the economic products are not produced until several years after planting. The use of DNA markers for selection in such crops could greatly reduce the number of breeding cycles needed. As such, the primary aim of this project was to map the oil palm genome by using restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP) and microsatellite (SSR) markers, in order to provide markers for selection in the breeding programme. A progeny derived from the selfing of a tenera guineensis palm (palm Tl28), which was segregating for the economically important monogenic characters of shell thickness and fruit color, was used for linkage map construction. A total of 523 segregating markers (117 RFLP, 22 SSR and 384 AFLP) were mapped to 17 linkage groups. In the current linkage map for the T128 palm, we have successfully mapped both the shell (Sh) gene and the fruit color (Vir) gene. Two RFLP markers mapped close to the Vir gene at a distance of 3 and 4 centiMorgans (eM), respectively. These two RFLP markers were tested by using seven other independent crosses segregating for this trait. The markers could predict the trait with about 95% certainty. The Sh gene was located about 8 cM from the nearest marker (EAGG/MCTT-250, an AFLP marker). The AFLP marker could distinguish the pisifera palms (absence of shell) from the dura (thick shell) and tenera palms (thin shell) in the mapping family evaluated. These markers are useful tools for application in a molecular breeding programme for oil palm. Analysis was also extended to include mapping of quantitative traits (QTLs) associated with oil quality. Oil quality is determined by the fatty acid composition (FAC) in oil palm. By using the genome wide threshold levels calculated independently for each of the traits, significant QTLs were identified for myristic acid (CI4:0), palmitic acid (CI6:0), palmitoleic acid (CI6:1) and stearic acid (CI8:0). In the attempt at mapping additional QTLs associated with oil quality, an interspecific cross between a Colombian oleifera (UP1026) and the Tl28 palm was also examined. A map consisting of 412 markers (302 AFLP, 83 RFLP and 27 SSR) in 18 linkage groups was generated at a LOD score of 5.0. At a genome wide significance threshold of P<O.OI and P<0.05, significant QTLs were detected for iodine value (IV), C14:0, CI6:0, C16:1 and CI8:0. There were common markers revealing significant linkages for the same trait in both the mapping families analyzed. Such tagging of markers to economically important traits will aid in expediting the production of elite planting materials with greater precision. To facilitate oil palm genome analysis leading to physical mapping and the identification of molecular markers associated with QTL and map based cloning, we attempted to develop the tools and techniques needed to construct a bacterial artificial chromosome (BAC) library for oil palm. A suitable method to purify and prepare the single copy vector (pBeloBACll) for BAC transformation was established. The proper partial digestion conditions of oil palm megabase DNA for BAC library construction were also determined. Several oil palm BAC clones were successfully identified. Hybridization of these BAC clones with oil palm DNA as probe confirmed the presence of oil palm DNA in those clones. In map based cloning efforts, cosmid libraries (with cloning capacity of up to 50 kb) are useful tools to complement BAC libraries. For this reason we constructed a cosmid library for oil palm. The library contains 65,000 clones with insert size ranging from 30 kb to 42 kb. Hybridization of randomly selected cosmid clones with oil palm DNA also confirmed the presence of oil palm DNA in these clones.